Genetic parameters, genomic prediction, and identification of regulatory regions located on chromosome 14 for weight traits in Nellore cattle - Teodoro, Miller [UNESP]; Maiorano, Amanda Marchi; Campos, Gabriel Soares [UNESP]; de Albuquerque, Lúcia Galvão [UNESP]; de Oliveira, Henrique Nunes [UNESP] (Wiley, 2025)
This study aimed to investigate functional variants in chromosome 14 (BTA14) and its impact in genomic selection for birth weight (BW), weaning weight (WW), and yearling weight (YW) in Nellore cattle. Genetic parameter estimation and the weighted single-step genomic best linear unbiased prediction (WssGBLUP) analyses were performed. Direct additive heritability estimates were high for WW and YW, and moderate for BW. Trait-associated variants distributed across multiple regions on BTA14 were observed in the weighted single-step genome-wide association studies (WssGWAS) results, implying a polygenic genetic architecture for weight in different ages. Several genes have been found in association with the weight traits, including the CUB And Sushi multiple domains 3 (CSMD3), thyroglobulin (TG), and diacylglycerol O-acyltransferase 1 (DGAT1) genes. The variance explained per SNP was higher in six functional classes of gene regulatory regions (5UTR, CpG islands, downstream, upstream, long non-coding RNA, and transcription factor binding sites (TFBS)), highlighting their importance for weight traits in Nellore cattle. A marginal increase in accuracy was observed when the selected functional variants (SV) information was considered in the WssGBLUP method, probably because of the small number of SV available on BTA14. The identified genes, pathways, and functions contribute to a better understanding of the genetic and physiological mechanisms regulating weight traits in the Nellore breed.
Keywords: Bos indicus; functional classes; genomics; GWAS; variants